Bimbingan Perkawinan Pranikah bagi Calon Pengantin di Kantor Urusan Agama - Siregar, Zulfahman; Kustati, Martin; Amelia, Rezki; Rajab, Rajab (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Marriage is a covenant that legitimizes the interaction between men and women who are not mahrams, thereby establishing rights and obligations between them. Marriage will be a harmonious, loving, and compassionate family, namely a peaceful, loving, and caring family. This will be achieved if the prospective spouses have knowledge in planning a quality family and possess skills in managing the family. However, the reality is that many married couples are unable to maintain their households or experience divorce between husband and wife. This is because they lack the knowledge to plan a quality family and the skills to manage it. The purpose of premarital marriage guidance activities for prospective brides and grooms at the Office of Religious Affairs in the Kuranji District of Padang City is to guide prospective brides and grooms so that they have knowledge in planning a quality family and possess skills in managing a harmonious, loving, and compassionate family. The methods used in premarital marriage guidance activities for prospective brides and grooms include discussion, question and answer sessions, and visualization of the beauty and challenges of married life. The result of premarital marriage guidance activities for brides-to-be is that every candidate who will marry has knowledge in planning a quality family and has skills in managing the family so that sakinah-mawaddah-wa-rahmah hospitality is realized.